ÖĞRETMEN ADAYLARININ EPİSTEMOLOJİK İNANÇLARI - Erten, Pınar; Kazu, İbrahim Yaşar (Dicle Üniversitesi, 2015)
Bireysel özellik olan epistemolojik inançların öğrenme üzerine olan etkileri bulunmaktadır. Bireylerin bilgileri işleme, yorumlama, kavrama durumları, ders çalışma stratejileri, problem çözme durumları, öğrenmeye yönelik çaba ve zamanları gibi durumlarda epistemolojik inançların etkileri mevcuttur. Bu çalışma ile öğretmen adaylarının epistemolojik inançlara ne düzeyde sahip oldukları cinsiyet, bölüm ve akademik ortalamalarına göre belirlenmeye çalışılmıştır. Öğretmen adaylarının epistemolojik inançlar açısından öğrenmenin çabaya bağlı olduğu inanç boyutu en fazla gelişmiş olduğu inanç boyutudur. Cinsiyet ve akademik ortalama açısından epistemolojik inançların boyutları arasında anlamlı bir farklılık bulunmamıştır. Epistemolojik inançların boyutlarında erkek ve kız öğrenciler eşit, not ortalaması yüksek olan öğrencilerinde yüksek düzeyde geliştiği sonucuna ulaşılmıştır. Bölüm değişkenine göre öğrenmenin çabaya ve yeteneğe bağlı olduğu inancı boyutlarında bir farklılaşma bulunurken, tek bir doğrunun var olduğu inancı boyutuna yönelik herhangi bir farklılaşma bulunmamıştır. Aritmetik ortalamalarından, Fen Bilgisi Öğretmenliği bölümü öğrencilerinin öğrenmenin çabaya, Sınıf Öğretmenliği bölümü öğrencilerinin öğrenmenin yeteneğe bağlı olduğuna ve Okul Öncesi Öğretmenliği bölümü öğrencilerinin tek bir doğrunun var olduğuna inançlarının az gelişmiş olduğu belirlenmiştir. Bu sonuçlar dikkate alınarak, diğer araştırmacıların, öğretmen adaylarının epistemolojik inançlarının geliştirilmesinde daha farklı çalışmalara gidilmesi sağlanabilir.

Epistemological beliefs, which are personal features, have effects on learning. They also have effects on information processing, interpreting, comprehending conditions, study strategies, problem solving, efforts and time allocated for learning of individuals. In this study, it has been aimed to determine at what level pre-service teachers’ have epistemological beliefs according to their gender, department, and academic average. Research prepared descriptive was carried out on 367pre-service teachers’. Epistemological beliefs scale was used for collecting the data. So the percentage of data, frequency, mean, standard deviation, independent sample t-test, one way analysis of variance, LSD test and Mann-Whitney U (MWU) test was used for analysis. The analysis results to be due to the efforts of pre-service teachers’ in the learning dimension of faith in terms of epistemological beliefs it has been identified as the belief that the more advanced dimensions. In terms of gender and academic average, it has not been found out a significant difference between the dimensions of epistemological beliefs. In the dimensions of epistemological beliefs, it has been concluded that the boys and the girls are equal, and that the epistemological beliefs of the students with a high grade point have developed at high level. According to department variance, while it has been found that there is a differentiation in the dimensions of beliefs which say that learning is up to effort and ability, it has not been found that there is a kind of differentiation towards the belief dimension which says that there is only one truth. By their academic average, it has been determined that the students of science teaching believe that learning is up to effort, the students of classroom teaching believe that the learning is up to ability and that the belief of the students of pre-school teaching, which says that there is only one truth, is underdeveloped. By taking into consideration these results, it could be ensured that other researches do different studies to improve pre-service teachers’ epistemological beliefs
Investigation of Pre-Service Teachers’ Epistemological Beliefs